(untitled) (In situ, 2024)
Archaeological rescue excavations were conducted in the port of Stinica in May 2022, in the area of the construction of toilet facilities in the port. The excavations in Stinica have shown that a cultural layer associated with the period of ancient Ortoplea extends in this area as well.